The silent persuader: Exploring the role of nonverbal customer interactions in shaping restaurant revisit intenti - Abd Hakim, Fairuz; Sulaiman, Suria; Mohd Akhir, Irina; Bahari, Khairil Anuar; Mazlan, Nor Hafizah; Husain, Zynoreen (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the impact of nonverbal customer-to-customer interactions (NVCCI) on customers’ revisit intentions in Malaysian restaurants. While customer-to-customer interaction (CCI) is recognised as influential, limited research focuses on nonverbal cues such as kinesics, proxemics, paralanguage, and physical appearance. Guided by the Stimulus-Organism-Response (S-O-R) framework, this study examines how these NVCCI dimensions shape dining experiences and revisit intentions. Using a quantitative survey with 195 respondents analysed via SPSS, results showed that kinesics (β = 0.389), proxemics (β = 0.164), and paralanguage (β = 0.212) significantly and positively influenced revisit intention, while physical appearance had no significant effect. The model explained 45% of variance in revisit intention (R² = 0.450). These findings highlight the importance of body language, personal space, and vocal tone in enhancing customer satisfaction and loyalty, with kinesics as the strongest predictor. This study contributes to NVCCI literature in hospitality and offers practical insights for managers to foster positive nonverbal interactions to encourage repeat visits.